It Came From the 1950s! - Jones, Darryl. author. aut Link
XIV, 262 p.
Keywords: An eclectic and insightful collection of essays predicated on the hypothesis that popular cultural documents provide unique insights into the concerns, anxieties and desires of their times. 1950s popular culture is analysed by leading scholars and critics such as Christopher Frayling, Mark Jancovich, Kim Newman and David J. Skal.